STUDI KARAKTERISTIK MATERIAL STEM SEPEDA UNTUK PENGEMBANGAN PROTOTIPE STEM SEPEDA BERBASIS LIMBAH PISTON DENGAN VARIASI TEMPERATUR CETAKAN - Suganda, Cecep; Sutoyo, Edi; Yuliaji, Dwi (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2018)
Bicycle stem is the link between handlebar (handlebar) with steerer tube (fork). Stem one of the bike parts to note and Each type of bike is different for the size and specifications stemnya. This research aims to. Obtained characterization of alumunium casting material as a material for making stem bikes with casting temperature of 700 ° C, and temperature variations of room temperature (30 ° C), 100 ° C, 150 ° C, 200 ° C, and characteristic hardness values stem between piston waste material and stem. The piston waste is melted at the melting furnace at a temperature of 700 ° C. then cast into the mold. After obtaining the specimen and then testing the material characteristics include chemical composition, microstructure, and hardness. The result of the research after casting with variation of the molded temperture has different material characteristic values, ie: chemical composition which has no change before and after casting, the microt structure has little porous defect, and the hardness value where the higher the mold temperature the lower the hardness . Conclusions of data processing The highest value of piston recycled hardness is 93 HV when compared to the hardness of 61.2 HV stem bike material, the hardness is more than enough and from the composition test there is a difference of Si 12% composition. Result of micro structure at foundry with 4 variation still have defect of cast (porous and shrinkage). the stam bike hardness test has an average hardness value of 64.2 HV whereas for the hardness value of piston waste casting results show the hardness value of 91 HV with mold temperature 30 ° C, 93 HV with mold temperture 100 ° C, 89 HV with mold temperature 150 ° C, 87 HV with mold temperature 200 ° C. The higher the mold temperature, the lower the hardness of the material.